Antioxidant-phenolic content correlation of phenolics rich fractions from Dillenia suffruticosa wood bark - Rini Muharini; Ira Lestari; Masriani Masriani (Universitas Ahmad Dahlan, 2021)
Dillenia suffruticosa is one of the tropical medicinal plants that has been used traditionally for treating several tropical diseases. However, phytochemical and pharmacological investigations of D. suffruticosa wood bark have not been well-investigated. This research aimed to investigate the correlation between antioxidant properties and total phenolic content of phenolics rich extract and fractions from D. suffruticosa wood bark. The phytochemical investigation revealed the existence of phenolics and alkaloids in methanolic crude wood bark extract and all fractions. Meanwhile, the presence of flavonoids was shown in chloroform and methanol fractions. The highest total phenolic content was demonstrated by methanol fraction with 254.34 Â± 16.86 mg GAE/g extract. Meanwhile, the highest total flavonoid content was interestingly displayed in chloroform fraction with 15.33 Â± 0.26 mg RE/g extract. The crude extract and methanol fraction had a profound antioxidant activity with IC50 values of less than 15.63 ppm and 8.83 ppm, respectively. A strong correlation was shown between the antioxidant activity and total phenolic contents through correlation analysis. Thus, the D. suffruticosa wood bark could be considered a potential natural source of antioxidants.